2009
DOI: 10.1002/dneu.20705
|View full text |Cite
|
Sign up to set email alerts
|

Age‐dependent differential expression of genes involved in steroid signalling pathway in the brain of protandrous black porgy, Acanthopagrus schlegeli

Abstract: ABSTRACT:The mechanisms underlying brain sex differentiation in animals are poorly understood. In the present study, using black porgy, Acanthopagrus schlegeli, as primary experimental model, we investigated the temporal expression patterns of receptors for androgen (ar) and estrogen (esr1 and esr2a) in the brain during posthatching ages and analyzed them against the timing of gonadal germ cell development. We hypothesized that endogenous estrogens naturally masculinize the brain of black porgy. The expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…This significant increase in the mRNA of StAR, considering its rate-limiting function and its role in the regulation of neurosteroidogenesis, also suggested a functional significance in the brain. Developmental expression changes of StAR have been reported in the protandrous black porgy brain, which showed high expression from 75 dah with significant increases at 120 dah in the forebrain and hypothalamus [6]. Moreover, Kim et al [55] reported that StAR mRNA was expressed at very low levels in various brain regions of the rat after adrenalectomy and gonadectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This significant increase in the mRNA of StAR, considering its rate-limiting function and its role in the regulation of neurosteroidogenesis, also suggested a functional significance in the brain. Developmental expression changes of StAR have been reported in the protandrous black porgy brain, which showed high expression from 75 dah with significant increases at 120 dah in the forebrain and hypothalamus [6]. Moreover, Kim et al [55] reported that StAR mRNA was expressed at very low levels in various brain regions of the rat after adrenalectomy and gonadectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression of ER˛, ERˇ1 and ERˇ2 was identified in different tissues of the fathead minnow (Pimephales promelas) during early development and in adults, indicating different mechanisms of regulation for the different ERs [41]. Tomy et al [6] reported that these two ER subtypes were expressed in the brain of male black porgy from 75 dah with a later peak during gonadal sex differentiation. The above observations suggest functional roles of each ER in adult and during early developmental ages, although the exact physiological roles of each ER subtype in neurosteroidogenesis with respect to brain development require further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression was about 30 times lower in the gonads than in the brain (Halm et al, 2003). Later, P450c17 expression was detected in the brain of different fish species, including the rice field eel (Yu et al, 2003), black porgy (Tomy et al, 2007, 2009), zebrafish (Wang and Ge, 2004; Diotel et al, 2011a), and rainbow trout (Vizziano-Cantonnet et al, 2011). In the tongue sole ( Cynoglossus semilaevis ), semiquantitative RT-PCR showed that cytochrome P450c17 was predominantly expressed in the ovaries and the brain (Chen et al, 2010a).…”
Section: Expression Of the Main Steroidogenic Enzymes In The Fish Brainmentioning
confidence: 99%
“…Other roles for SF-1 include regulation of feeding and sexual differentiation. In the protandrous black porgy, Acanthopagrus schlegeli , NR5A2 has been shown to be positively correlated in expression, along with androgen and estrogen receptors, during sexual differentiation of the brain (Tomy et al, 2009). Of interest in the current study is that when small molecules were overlaid onto the gene pathway, the NR5A1 and NR5A2 expression network in dieldrin + E 2 fed males also included testosterone and progesterone.…”
Section: Discussionmentioning
confidence: 99%